Design and Development of the Architecture and Framework of a Knowledge-Based Expert System for Environmental Impact Assessment - Jazzar, Moneef Mohammad Abdel-Kareem (2000)
The development of the architecture and framework of a knowledge-based expert system (ES) named "JESEIA" for environmental impact assessment (EIA) was developed using the C Language Integrated Production System (CLIPS) that incorporates relevant expert knowledge on EIA and integrates a computational tool to support the preparation of an EIA study. The research was based on the conceptualization and development of the architecture and framework of a knowledge-based expert system that demonstrates the feasibility of integrating the following aspects: Expert knowledge-based system approach, Object-oriented techniques and rules structuring as knowledge modeling paradigm, database management system as a repository connection between domain knowledge sources and the expert system kernel, and finally EIA as a significant knowledge domain and incremental approach as a development model. This work describes the functional framework of combining shared knowledge from various experts as knowledge sources through the implementation of a blackboard system approach that organizes the solution elements and determines which information has the highest certainty to contribute to the inference solution. The rules, in the rule base, were developed according to the environmental component classification characteristics with attributes in an object-oriented technique. The developed system considers the robustness, expandability and modularity throughout its development process. The raw knowledge and database were kept in a supportive data base developed in the system for further reference or updating through the developed expert system as a built-in functionality as well as through a connection to an external data base environment through an open database connectivity mechanism.